A low‐profile ultrawideband circularly polarized slot antenna array based on artificial magnetic conductor array reflector. Issue 7 (25th April 2022) - Zhang, Jinping; Xing, Zijian; Li, Jianying; Luo, Dingyi; Sim, Chow‐Yen‐Desmond
Abstract: A broadband circularly polarized (CP) slot antenna unit that is composed of a sector‐shaped radiator and an irregular pentagon slot ground plane is initially investigated. The CP characteristics are realized based on unbalanced feeding and loading of irregular slot structure. To increase the gain and yield ultrawideband operation, a 2 × 2 antenna array with a sequential rotational feeding method is introduced. To further reduce the total profile of the proposed antenna array to 0.15λ0, an artificial magnetic conductor array reflector is loaded between the antenna array and the feeding network. The measured 10‐dB impedance bandwidth of the proposed antenna array was 82.6% (8.31–20.0 GHz), and its corresponding CP bandwidth was 65.4% (8.61–16.98 GHz), and the radiation efficiency of the antenna is also higher than 80%. Besides exhibiting very good axial beams across the wide CP bandwidth, a peak gain of up to 11.1 dBic is also achieved. Thus, it is suitable for X‐band and Ku‐band satellite communication applications.